Deconstructing Racial Paradigms in Criminology: Towards an Inclusive and Critical Approach - Wang Suyi (Eximia, 2024)
This paper critiques the conventional frameworks in criminological research regarding race and racism. It identifies the limitations of data-driven methods that often perpetuate racial stereotypes due to biased and incomplete data. The study argues that criminology has historically minimized the role of race, treating it as a mere variable and neglecting the broader socio-political contexts. This oversight leads to color-blind racism, which ignores systemic inequalities and fails to account for the lived experiences of minority communities. Furthermore, the paper highlights the emerging issue of racial biases embedded in artificial intelligence tools used in criminology, which can exacerbate discrimination. The author advocates for a reorientation of criminological research to incorporate minority perspectives and analyze data within both historical and contemporary contexts. This approach aims to provide a more nuanced understanding of the interplay between race and criminal behavior, thereby promoting a more inclusive and equitable criminological practice.